Phage-encoded depolymerases as a strategy for combating multidrug-resistant Acinetobacter baumannii - Islam, Md Minarul; Mahbub, Nasir Uddin; Shin, Woo Shik; Oh, Man Hwan (Frontiers in Cellular and Infection Microbiology, 2024)
Acinetobacter baumannii, a predominant nosocomial pathogen, represents a grave threat to public health due to its multiple antimicrobial resistance. Managing patients afflicted with severe infections caused by multiple drug-resistant A. baumannii is particularly challenging, given the associated high mortality rates and unfavorable prognoses. The diminishing efficacy of antibiotics against this superbug underscores the urgent necessity for novel treatments or strategies to address this formidable issue. Bacteriophage-derived polysaccharide depolymerase enzymes present a potential approach to combating this pathogen. These enzymes target and degrade the bacterial cell’s exopolysaccharide, capsular polysaccharide, and lipopolysaccharide, thereby disrupting biofilm formation and impairing the bacteria’s defense mechanisms. Nonetheless, the narrow host range of phage depolymerases limits their therapeutic efficacy. Despite the benefits of these enzymes, phage-resistant strains have been identified, highlighting the complexity of phage-host interactions and the need for further investigation. While preliminary findings are encouraging, current investigations are limited, and clinical trials are imperative to advance this treatment approach for broader clinical applications. This review explores the potential of phage-derived depolymerase enzymes against A. baumannii infections.